Palco de Encontros: arte no ensino médio tecida através da inventividade no teatro e na vida - Almeida, Francira Mota de Matos (2024)
This research aims to monitor, analyze and reflect on the the atrical f ormative creative process Palco d e Encontros ””, developed at the Deputado Fernando Mota High School, located in the city of Tejuçuoca (CE). M eeting the other, i n the relationshi ps of the shared experience of the practice in the classroom, an acti on that t akes place in playing a theatrical game with high school students, denotes the key to accessing this research How can a pedagogical artistic proposal trigger fo rmative processes, encounters and life transformations in the school environment? How can the n otion of invention act as a driving word for the teaching and learning relationship from the perspective of t h eatrical language? This research is based on experi ences arising from the crossings and affectations of the artist teacher and author of this rese arch, founder of the Berro Theater Group, bo rn over 19 years ago, on the floor of the Deputado Fernando Mota H igh School, in the backlands of Cea rá . The methodol ogical path was developed in two stages, the first being carried out in the elective c ourse of Theatrical Initiation, during the first semester of 2022, and the second during the creative meetings to put t ogether the Palco d e Encontros sketch, which took place in the second semester of 2022. The reflection and writing of this research is based on materials recorded and produced from students' logbooks, photos, videos and audios, as well as critical refle c tion based on theoretical refere nces, including: In ventive Cognition (KASTRUP, 2007); Theatrical Conviviality (DUBATTI, 2017); Meeting ( GROTOWSKI , 1976; FIADEIRO & EUGÊNIO , 2012) and Creative Process (SALLES, 2008). Finally, this investigation, developed together with the Professional Ma ster's Degree in Ar ts ICA/UFC, sought to weave pedagogical and artistic reflections based on the notion of invent ion and the experience of the encounter between bodies that teach and learn in the school environment.